2021
DOI: 10.1038/s41598-021-84783-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the gut microbiome and fatigue in cancer patients

Abstract: Fatigue is the most prevalent symptom of cancer and its treatments. Changes in the intestinal microbiome have been identified in chronic fatigue syndrome and other neuropsychiatric disorders, and cancer patients. However, the association between intestinal microbiome and fatigue in patients with advanced cancers has not been evaluated. Understanding the connection between intestinal microbiome and fatigue will provide interventional and therapeutic opportunities to manipulate the microbiome to improve fatigue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
2
25
1
Order By: Relevance
“…Possible ways to gain such insights would involve analyzing stored serum or plasma samples collected from large registration trials for changes in cytokines and correlation with patient-reported fatigue. Recently gut microbiome has been associated with fatigue [9] and it will be interesting to explore its role in ICIrelated fatigue. There is also a need to investigate various approaches to help mitigate the burden of fatigue including cytokine antagonists, other pharmacotherapies such as methylphenidate, and interventions such as cognitivebehavioral therapies, mind-body therapies, and supervised exercise programs [6,7].…”
Section: Immunotherapy and Fatigue: What We Know And What We Don't Know Muhammad Azeem Khan Vaia Florou And Umang Swamimentioning
confidence: 99%
“…Possible ways to gain such insights would involve analyzing stored serum or plasma samples collected from large registration trials for changes in cytokines and correlation with patient-reported fatigue. Recently gut microbiome has been associated with fatigue [9] and it will be interesting to explore its role in ICIrelated fatigue. There is also a need to investigate various approaches to help mitigate the burden of fatigue including cytokine antagonists, other pharmacotherapies such as methylphenidate, and interventions such as cognitivebehavioral therapies, mind-body therapies, and supervised exercise programs [6,7].…”
Section: Immunotherapy and Fatigue: What We Know And What We Don't Know Muhammad Azeem Khan Vaia Florou And Umang Swamimentioning
confidence: 99%
“…Recently, several studies reported an association between gut microbiome and feelings of fatigue [ 38 , 39 , 40 , 41 ]; however, these studies did not distinguish between the mental and physical aspects of fatigue. These preliminary findings have reported reduced diversity and altered gut microbiome among patients with cancer-related fatigue [ 38 , 40 ] and myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) [ 39 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies reported an association between gut microbiome and feelings of fatigue [ 38 , 39 , 40 , 41 ]; however, these studies did not distinguish between the mental and physical aspects of fatigue. These preliminary findings have reported reduced diversity and altered gut microbiome among patients with cancer-related fatigue [ 38 , 40 ] and myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) [ 39 , 41 ]. These studies were exploratory in nature, with some studies not adjusting analyses to account for multiple comparisons [ 38 , 40 , 41 ] and others comparing ME/CFS patients to healthy control populations [ 39 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations